Succession Planning and Sustainability of Family Businesses and in South-East, Nigeria - Dike, Goodfaith N.; Idemobi, Ellis I.; N. Okafor, Chisom; I. Anyika, Michael; Obiezekwem, Jeffery Chukwujekwu; Nwankwo, Ekene Ezinwa (British Journal of Marketing Studies, 2025)
This study aimed at identifying the effect of succession planning and sustainability of family businesses and in south-east, Nigeria. The overall objective of this research was; to determine the effect of mentoring, financing decisions and job rotation of successors on sustainability of family businesses in south-east, Nigeria. This work was anchored on social exchange theory. A descriptive survey research design was used and the population was 1060. The sample size for the study was determined using borg and gall (1973) formula which was given as 203. Data collected through the questionnaire were described using descriptive statistics while Pearson product moment coefficient of correlation was employed to test the hypotheses. This study however, has shown that mentoring positively influences sustainability of family businesses in south-east, Nigeria with tcal (3.377) and ttab (2.35); finance decisions positively influence sustainability of family businesses in south-east, Nigeria with tcal (3.377) and ttab (2.35); job rotation positively influences sustainability of family businesses in south-east, Nigeria with tcal (3.377) and ttab (2.35). The study concluded that succession planning has a significant positive effect on sustainability of family businesses in south-east, Nigeria. Based on the findings, the study recommended that management of family businesses should develop mentorship program that will enable young successors to acquire necessary skills, knowledge, and capabilities needed to address leadership challenges, and cultivate the right ethical culture for family business sustainability.